2020
DOI: 10.1097/cm9.0000000000000791
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of glucocorticoid therapy in patients with severe coronavirus disease 2019: protocol of a randomized controlled trial

Abstract: Background: At the end of 2019, a novel coronavirus outbreak emerged in Wuhan, China, and its causative organism has been subsequently designated the 2019 novel coronavirus (2019-nCoV). The effectiveness of adjunctive glucocorticoid therapy in the management of 2019-nCoV-infected patients with severe lower respiratory tract infections is not clear, and warrants further investigation. Methods: The present study will be conducted as an open-labeled, randomized, controlled trial. We will enrol 48 subjects from Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(78 citation statements)
references
References 47 publications
0
73
0
5
Order By: Relevance
“…As shown in Figure 1, among 31 initially included studies (14 in English and 17 in Chinese), eight were reviewed as full-text and four finally included (14)(15)(16)(17). Two studies were excluded since they were commentaries (9, 10), one excluded as it was a protocol (18), and one a letter to Editor (19). Table 1 shows the descriptive characteristics of the four included studies.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 1, among 31 initially included studies (14 in English and 17 in Chinese), eight were reviewed as full-text and four finally included (14)(15)(16)(17). Two studies were excluded since they were commentaries (9, 10), one excluded as it was a protocol (18), and one a letter to Editor (19). Table 1 shows the descriptive characteristics of the four included studies.…”
Section: Search Resultsmentioning
confidence: 99%
“…Importantly, one study identified in this review in patients with ARDS owing to COVID-19 infection showed that methylprednisolone significantly decreased the risk of mortality. It should be noted that there is currently one ongoing clinical trial that is directly addressing this research question and its results are eagerly awaited (18).…”
Section: Discussionmentioning
confidence: 99%
“…Ongoing clinical trials are being conducted at this moment to confirm their role. ChiCTR2000029386 is a randomized clinical trial currently being conducted in China on 48 patients and methylprednisolone to be administrated to half of them like a dose of 1-2 mg/kg/day for 3 days [123]. Other studies also registered for Clinicaltrials.gov and currently in the process of recruiting patients.…”
Section: Corticosteroids (Methylprednisolone In Particular)mentioning
confidence: 99%
“…Currently, the following drugs are most often used to treat coronavirus infection: the combination of the antiviral drugs lopinavir/ritonavir [68], nucleotide analogs that inhibit RNA-dependent-RNA polymerize of the virusribavirin [69] and remdesivir [70], antimalarial drug hydroxychloroquine (less toxic analog of chloroquine) [71], sometimes in combination with the antibiotic azithromycin [72], and the glucocorticoid methylprednisolone [73]. According to a recent study on lopinavir/ritonavir, the combination of drugs used to treat AIDS did not show any benefits compared to standard hospitalization [74].…”
Section: Melatonin Can Be Utilized In Combinations With Drugs and Trementioning
confidence: 99%